The RPTRA Geographic Information System Application in Central Jakarta City Using the Dijkstra Algorithm Based on Android - Sugiharja, Danur; Pahlevi, Omar; Widyastuti, Reni (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Child Friendly Integrated Public Space or also known by the abbreviation RPTRA is the concept of public space in the form of green open spaces or parks that are equipped with various interesting games. Currently RPTRA is already widely available in all DKI Jakarta, especially in Central Jakarta, but there are still many people who do not know the location of the location of RPTRA. The dijkstra algorithm applied to this Android-based RPTRA geographic information system application in the City of Central Jakarta is to use google maps as a navigation map, where the Algorithm: {When users select the Map menu in the main menu, users will see maps and points of all RPTRA locations in Central Jakarta City, select one of the RPTRA location points, after the user selects one RPTRA location point, select the image on the right bottom route, then the user will go to google maps to get the route to the selected RPTRA. } The location of RPTRA directly takes coordinates at each RPTRA located in Central Jakarta City. The results achieved in testing the application went well able to provide accurate data on the location points of RPTRA in Central Jakarta.